DIGITAL TRANSFORMATION IN LOCAL GOVERNANCE: OPPORTUNITIES, CHALLENGES AND STRATEGIES - Debbarma, Asmita; Chinnadurai, Ajay Sharma (RADJA PUBLIKA, 2023)
In the modern age, technology and government are working together to reshape the local administration. The study thoroughly explores how digital changes are impacting local governance, discussing their advantages, obstacles, and approaches. It emphasises the importance of using advanced technology to improve how efficiently administrations work, engage citizens, and make decisions based on data. It also acknowledges challenges such as unequal access to technology, cyber threats, resistance to change, financial limitations, and privacy concerns. Strategies proposed to tackle these challenges include ensuring widespread tech access, enhancing cybersecurity, involving stakeholders, fostering innovation, optimising resources, enforcing strict data protection rules, and empowering the workforce. The paper advocates for a comprehensive approach that considers various aspects to revolutionize local governance by integrating technology in ways that offer opportunities but also present intricate challenges. This approach aims to enhance administrative efficiency, citizen engagement, and data-driven decision-making in local governance.